Steric Control in Activator‐Induced Nucleophilic Quencher Detachment‐Based Probes: High‐Contrast Imaging of Aldehyde Dehydrogenase 1A1 in Cancer Stem Cells. Issue 11 (23rd November 2022) - Oe, Masahiro; Suzuki, Kanae; Miki, Koji; Mu, Huiying; Ohe, Kouichi
Abstract: Turn‐on fluorescence probes can visualize the enzyme activity with high contrast. We have established a new turn‐on mechanism, activator‐induced nucleophilic quencher detachment (AiQd), and developed AiQd‐based turn‐on fluorescence probes for the detection of enzymes. Herein, we demonstrate that the precise steric control efficiently quenches the fluorescence of AiQd‐based turn‐on probes before the enzymatic transformation. Theoretical calculation appropriately predicted the ratio of the fluorescence‐quenched closed‐ring form of probes. βC5S‐A, which has a sterically demanding methyl group at the β‐position of a fluorescence‐quenching nucleophilic mercapto group, showed a low background signal. βC5S‐A responded to aldehyde dehydrogenase 1A1 (ALDH1A1) with high selectivity, thereby enabling high‐contrast live imaging of cancer stem cells (signal‐to‐noise ratio >10). The ALDH1A1‐responsiveness of βC5S‐A was not significantly affected by amino acids and biological thiols, such as cysteine and glutathione. Abstract : The turn‐on fluorescence probe βC5S‐A for aldehyde dehydrogenase 1A1, which is a biomarker of cancer stem cells, was synthesized. The steric effect of a methyl group introduced in βC5S‐A enhanced the robustness of its fluorescence‐quenched closed‐ring form, supressing the background signal. βC5S‐A successfully visualizes cancer stem cells with high contrast (signal‐to‐noise >10) in in vitro experiments.